2014
DOI: 10.1007/s11892-014-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Getting a Technology-Based Diabetes Intervention Ready for Prime Time: a Review of Usability Testing Studies

Abstract: Consumer health technologies can educate patients about diabetes and support their self-management, yet usability evidence is rarely published even though it determines patient engagement, optimal benefit of any intervention, and an understanding of generalizability. Therefore, we conducted a narrative review of peer-reviewed articles published from 2009–2013 that tested the usability of a web- or mobile-delivered system/application designed to educate and support patients with diabetes. Overall, the 23 papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 40 publications
(29 reference statements)
3
56
0
Order By: Relevance
“…The true spirit of user-centered design 13 is to ensure accessibility and functionality across a diverse group of end users, and yet we rarely employ these strategies in creating health technologies. A recent review we conducted found that not only were usability studies of diabetes technologies rarely published, but also that the existing usability studies often did not report on the characteristics of their user populations 14 -suggesting that limited health literate or low-income groups are almost never included in the design phase. Again, this usability issue might be further amplified with widespread online portal use as a part of Meaningful Use, as the data from integrated systems like Kaiser with longstanding portal access show that racial/ ethnic minorities and those with limited health literacy are less likely to use these websites.…”
mentioning
confidence: 99%
“…The true spirit of user-centered design 13 is to ensure accessibility and functionality across a diverse group of end users, and yet we rarely employ these strategies in creating health technologies. A recent review we conducted found that not only were usability studies of diabetes technologies rarely published, but also that the existing usability studies often did not report on the characteristics of their user populations 14 -suggesting that limited health literate or low-income groups are almost never included in the design phase. Again, this usability issue might be further amplified with widespread online portal use as a part of Meaningful Use, as the data from integrated systems like Kaiser with longstanding portal access show that racial/ ethnic minorities and those with limited health literacy are less likely to use these websites.…”
mentioning
confidence: 99%
“…In this framework several qualitative and quantitative evaluation methods have been proposed. Mixing qualitative and quantitative evaluation methods ensures comprehensive data collection and avoids needless a priori assumptions [26,34,36]. However, there are also limitations of using the conceptual framework of De Bleser et al This framework is not widely adopted in usability testing and although it builds on existing literature and frameworks it remains unclear how valid this conceptual framework itself is.…”
Section: Discussionmentioning
confidence: 99%
“…User performance was studied using three methods: (1) counting errors of use during the performed tasks; (2) timing user tasks in seconds; (3) asking participants to think aloud while performing tasks. A think-aloud method is commonly used in usability research, especially when users are confronted for the first time with a device [26,3436]. This method is used to make explicit what users thoughts and experiences are when performing a specific task.…”
Section: Methodsmentioning
confidence: 99%
“…User performance was studied using three methods: (1) counting errors of use during the performed tasks; (2) timing user tasks in seconds; (3) asking participants to think aloud while performing tasks. A think-aloud method is commonly used in usability research, especially when users are confronted for the first time with a device [26,[34][35][36]. This method is used to make explicit what users thoughts and experiences are when performing a specific task.…”
Section: Data Collectionmentioning
confidence: 99%